KAJIAN TENTANG PENGENALAN KARAKTER DENGAN METODE ANALYTIC SIGNAL VECTOR - Arif Januardi Liuman; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Book searching in the library is an activity that needs a lot of waste of time. Therefore, it is necessary to design a tool that can search for books based on charcter recognition. The characters willl eventually be recognized by the code contained books. The design is expected to help users for easy and practical searching of books. The method used in the paper is the Analytic Signal Vector (ASV). The ASV method works on the vectors of signals basis. The process of ASV method consists of several stages, starting calculating from Inverse Discrete Fourier Transform (IDFT) to obtain the analytical signal, finding the degree of similarity by using the Hermitian inner product, and calculating the Magnitude of Complex Number which is used to find the  similarity value from two complex numbers by using this method, it is expected that the characters can be recognized and the system can search the gueries properly